Resolving puzzling phenomena by the simple particle model: examining thematic patterns of multimodal learning and teaching. (2nd January 2020) - Cheng, Maurice M. W.; Danielsson, Kristina; Lin, Angel M. Y.
ABSTRACT: This paper examines the roles of multimodality and thematic patterns in the teaching of the particle model of matter. Although the particle model is a fundamental topic in science education, there is no consensus on (1) whether or not the model should be introduced in early grades and (2) how to introduce the model to students for the very first time. Drawing from teacher development projects in Sweden (Grade 3) and in Hong Kong (Grade 7), we suggest that the learning and teaching of the particle model can be facilitated by utilising a variety of modes. With multimodal scaffolding, Grade 3 students were able to demonstrate aspects of the particle model related to the expansion of gases in a warmer environment. The paper illustrates teaching episodes from the two projects in terms of (i) aspects of the particle model that were constructed using different semiotic modes, (ii) shifts in the salience of different modes in the teaching and learning process, and (iii) a thematic pattern that the classroom interactions adopted to explain puzzling phenomena. For a theoretical advancement, we suggest that thematic analysis should be extended to multimodal interactions.